2009
DOI: 10.1111/j.1461-9563.2009.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Temptations of weevil: feeding and ovipositional behaviour of Hylobius warreni Wood on host and nonhost bark in laboratory bioassays

Abstract: 1 Warren root collar weevil Hylobius warreni Wood (Coleoptera: Curculionidae) is a long-lived, flightless insect native to coniferous forests across northern North America. Girdling by larval feeding causes significant mortality on young trees. The insect poses considerable challenges to reforestation. 2 Adult weevils feed on all life stages of a variety of coniferous hosts prior to oviposition. Their relative feeding preferences, however, have not been quantified. Moreover, it is not known whether host bark i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…These include prescribed burning and scarification to remove excess slash and stumps because this will disrupt the development of populations of Warren root collar weevil remaining in stands. We encourage the incorporation of less susceptible host tree species such as deciduous species into prescribed planting mixes because this may reduce weevil impacts (Hopkins et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include prescribed burning and scarification to remove excess slash and stumps because this will disrupt the development of populations of Warren root collar weevil remaining in stands. We encourage the incorporation of less susceptible host tree species such as deciduous species into prescribed planting mixes because this may reduce weevil impacts (Hopkins et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Warren root collar weevil is found throughout the boreal forests of North America. Adults weevils feed nocturnally on twigs, buds and foliage of both young and mature trees of a variety of conifers (Hopkins, Klingenberg & Aukema 2009), descending during dawn hours to rest in the duff layers consisting of moss, lichen and fine woody debris accumulated at the base of host trees. Both males and females are flightless throughout their life cycle, which may last up to 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…As the insects mature, their feeding galleries become deeper, and they may score the xylem tissues (Warren 1956, Cerezke 1994. In British Columbia, the weevilÕs primary host is lodgepole pine, Pinus contorta variety latifolia, although they feed on a variety of hosts in the Pinaceae family including species of Pinus, Picea, Abies, Larix, and Tsuga (Warren 1956, Wood 1957, Whitney 1961, Grant 1966, Wood and Van Sickle 1989, Cerezke 1994, Hopkins et al 2009). …”
mentioning
confidence: 98%
“…shown that H. warreni does feed more on its preferred lodgepole pine hosts, when compared to less preferred conifers and non-host angiosperms (Hopkins et al 2009). This presumably suggests some mechanism of host assessment once in contact with the host's tissues, although it is not clear if this is mediated by vision, chemoreceptors, or some other modality.…”
Section: Movement Rates and Patterns And A Population Estimate From Amentioning
confidence: 99%
“…Duke and Lindgren (2006) found that there were potential correlations between lodgepole pine trees previously attacked by individuals of H. warreni and concentrations of a-terpinolene, P-phellandrene, a-thujene and 8-3-carene, although there was no method to separate cause and effect of weevil attack. In addition, feeding bioassays of H. warreni have suggested individuals display some form of host recognition while feeding, as they fed more on preferred hosts (lodgepole pine), compared to less preferred conifers and non-host angiosperms, although it was unclear if this preference was related to the chemical composition of the trees (Hopkins et al 2009). …”
Section: Weevil Bioassaymentioning
confidence: 99%